A Novel Hydro Powered Online Power Converter for Marine Lighting Applications - Sinu KJ; G. Ranganathan (Institute of Advanced Engineering and Science, 2018)
This paper presents a new hydro energy based dc-dc PFC sepic based buck converter for marine lighting applications. The major advantage of the proposed power converter is high power factor and low THD with higher efficiency. SEPIC converter produces continuous smooth ripple free current because of two inductors in series in line in its circuit. Sepic converter produces lower switching losses because of lower voltage stress on power switch employed compared to other buck-boost converter topologies. Tidal wave energy is converted into mechanical energy with the help of a hydro turbine which drives a permanent magnet synchronous generator to produce three phase ac output voltage. It produces a low ac voltage which is converted into DC using passive diode rectifier and fed to sepic converter for voltage regulation as well as to improve quality of power supply such as high power factor, low THD. The proposed sepic based power converter for marine lighting application is simulated in MATLAB/Simulink environment for verifying the performance of proposed scheme.